An Analysis Of The Spring Water Potential Utilization For Bottled Water Production In Glempang Village, Banyumas Regency: Analisis Potensi Pemanfaatan Mata Air Untuk Air Kemasan Di Desa Glempang Kabupaten Banyumas - Muhammad Agung Nugroho; Rakhmad Maulidi; Eka Sahputra (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service activity aims to analyze the potential use of spring water for bottled water production in Glempang Village, Banyumas Regency, using the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method. The analysis results show that this village has great potential, supported by good water quality, a strategic location in the upstream area, high community participation, and existing infrastructure such as reservoirs. Local bottled water market opportunities and support from government programs create favorable conditions. However, there are challenges such as technical and financial limitations, inadequate infrastructure, and the threat of climate change and environmental degradation. The analysis results conclude that the development of the bottled water industry can be a model for a sustainable village economy, if managed well through strategic partnerships, capacity building, investment in appropriate technology, and a strong water quality management system.